2020
DOI: 10.1016/j.stemcr.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Retinal Pigment Epithelial Cells Derived from Human Embryonic Stem Cells Lacking Human Leukocyte Antigen Class I and II

Abstract: Human embryonic stem cell-derived retinal pigment epithelial (hESC-RPE) cells could serve as a replacement therapy in advanced stages of age-related macular degeneration. However, allogenic hESC-RPE transplants trigger immune rejection, supporting a strategy to evade their immune recognition. We established single-knockout beta-2 microglobulin (SKO-B2M), class II major histocompatibility complex transactivator (SKO-CIITA) and double-knockout (DKO) hESC lines that were further differentiated into corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 52 publications
(58 reference statements)
4
53
0
Order By: Relevance
“…Human RPE cell xenografts have also been shown to cause inflammation in the subretinal space of experimental animals, e.g., a human fetal RPE cell sheet transplantation into the subretinal space caused severe choroidal inflammation [11] or immunological rejection in rabbits [12]. When human embryonic stem cell-derived RPE cells (ESC-RPE cells; xenografts) were transplanted into the subretinal space of rabbits, these cells were also rejected [13][14][15]. In the present study, we used human iPSC-RPE cells as RPE xenografts that were transplanted into cynomolgus monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Human RPE cell xenografts have also been shown to cause inflammation in the subretinal space of experimental animals, e.g., a human fetal RPE cell sheet transplantation into the subretinal space caused severe choroidal inflammation [11] or immunological rejection in rabbits [12]. When human embryonic stem cell-derived RPE cells (ESC-RPE cells; xenografts) were transplanted into the subretinal space of rabbits, these cells were also rejected [13][14][15]. In the present study, we used human iPSC-RPE cells as RPE xenografts that were transplanted into cynomolgus monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…All of their gene‐edited cells suppressed both CD4 + and CD8 + T‐cell activation, but these edited cells enhanced NK cell activation, although they did not show a stronger cytotoxic activity than wild‐type (WT) hESCs. Furthermore, the edited cells were transplanted into a rabbit xenograft model without an immunosuppressive regimen, and the cells suppressed the early rejection response and delayed the production of anti‐human antibodies in the late rejection response 20 …”
Section: Preparation Methods Of Universal (Hypoimmunogenic) Hpscsmentioning
confidence: 99%
“…Several investigators have designed hPSCs in which B2M is knocked out ( Table 2). 5,[19][20][21][22][23][24][25][26][27] This is because the B2M protein forms a heterodimer with HLA class I proteins and is required for HLA class I expression on the cell surface ( Figure 2A). 11 Knocking out the B2M gene can restrict an immune response from cytotoxic CD8 + T cells by depleting all HLA class I molecules (HLA-A, -B, -C, -E, -F and -G), although B2M-knockout hPSCs become sensitive to natural killer (NK) cell-mediated killing because they lack the missing-self response ( Figure 2B(a)).…”
Section: Generation Of Universal Hpscs By Knocking Out B2mmentioning
confidence: 99%
“…Studies have demonstrated that MHC expression are of prime importance in allograft rejection and may be the precedent step to xenograft rejection 29,30 . Human breast cancer cells (MDA-MB-231), which express high-level HLA-ABC, were quickly rejected after transplanted into the striatum (Fig.S5A).…”
Section: Hla-abc Expression Was Not the Trigger For The Late-onset Rementioning
confidence: 99%